Analysis of a mechanical structure of a microscope sensor of atomic force / Atominių jėgų mikroskopo jutiklio mechaninės struktūros analizė - Andrius Dzedzickis; Vytautas Bučinskas (Mokslas: Lietuvos Ateitis, 2015)
Atomic Force Microscopy (AFM) is a method that allows obtaining an image of the surface of the sample in high resolution. This article investigates the problems associated with modeling a mechanical structure of a microscope sensor of atomic force.The paper refers to the previous scientists’ works and describes most frequently used methods of modeling, basic equations and a variety of factors that have an influence on the dynamics of the system. Also, the obtained results of earlier works are discussed.